2019
DOI: 10.1111/bjd.17582
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the emotional and behavioural reactions to receiving personalized melanoma genomic risk information: a qualitative study

Abstract: Summary Background There is a need for greater understanding of the spectrum of emotional and behavioural reactions that individuals in the general population may experience in response to genomic testing for melanoma risk. Objectives To explore how individuals in the general population respond to receiving personalized genomic risk of melanoma. Methods Semistructured interviews were undertaken with 30 participants (aged 24–69 years, 50% female, 12 low risk, eight average risk, 10 high risk) recruited from a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…A genetic counsellor communicated the information by telephone, and participants received an information booklet. A number of interesting findings emerged from this study: high‐risk individuals reported short‐term distress which resolved quickly; response to risk was influenced by pre‐existing expectations and, the majority of high‐risk and average‐risk individuals reported positive improvements in sun‐protective behaviours …”
mentioning
confidence: 86%
See 1 more Smart Citation
“…A genetic counsellor communicated the information by telephone, and participants received an information booklet. A number of interesting findings emerged from this study: high‐risk individuals reported short‐term distress which resolved quickly; response to risk was influenced by pre‐existing expectations and, the majority of high‐risk and average‐risk individuals reported positive improvements in sun‐protective behaviours …”
mentioning
confidence: 86%
“…In the current issue of the BJD , Fenton and colleagues explore the impact of melanoma risk communication . This qualitative study involved semi structured interviews with 30 individuals, never diagnosed with melanoma, who had received polygenic melanoma risk scores (categorized as low, average or high risk).…”
mentioning
confidence: 99%
“…Authors responded to our challenge with a wider range of submissions and almost double the number submitted last time, showing the growing interest in qualitative research in this field. Our second spotlight for summer 2019 showcases 10 studies, comprising a complementary mix of six original articles and four research letters . These papers involve interdisciplinary authorship teams from dermatology, psychology, general practice, nursing, public health and applied health services research in Australia, Germany, the Netherlands, the Republic of Ireland, the U.K. and the U.S.A.…”
mentioning
confidence: 99%
“…Six papers, demonstrate qualitative methods’ capacity to access psychological and social issues that are difficult to reach with traditional questionnaire/survey research, and the capability to investigate the portrayal and experience of the skin in the online world. Fox et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation